Selenium-enriched durum wheat improves the nutritional profile of pasta without altering its organoleptic properties. (1st January 2017) - De Vita, Pasquale; Platani, Cristiano; Fragasso, Mariagiovanna; Ficco, Donatella Bianca Maria; Colecchia, Salvatore Antonio; Del Nobile, Matteo Alessandro; Padalino, Lucia; Di Gennaro, Spartaco; Petrozza, Angelo
Highlights: Se-enriched pasta through foliar fertilization of durum wheat was evaluated. Se concentrations increased linearly according to the foliar Se application. Durum wheat landraces and obsolete varieties accumulated more grain Se than modern. High Se concentration was preserved even after a high rate of milling extraction. Se enrichment had no effects on grain quality and sensorial properties of pasta. Abstract: Two field experiments were conducted over three growing seasons (2006–07, 2008–09 and 2009–10) to evaluate Se-enriched pasta through foliar fertilization at various rates and timing of application on 4 durum wheat varieties. Our findings confirm the effectiveness of foliar Se fertilization to increase Se concentrations in durum wheat grain, even at high Se rates (120 g Se ha −1 ). Se fortification was significant across different genotypes, with greater Se accumulation in landraces ('Timilia') and obsolete varieties ('Cappelli'), with respect to modern varieties. The Se content in the grain was increased by up to 35-fold that of the untreated control. The Se concentration decreased during milling (11%), while processing and cooking of pasta did not show significant decreases. This biofortification stategy had no effects on grain quality parameters, except for reduced gluten index in the high-gluten variety PR22D89, as well as for the sensorial properties of the spaghetti.